Pressurised water flow in fractured permafrost rocks revealed by borehole temperature, electrical resistivity tomography, and piezometric pressure - M. Offer; M. Offer; S. Weber; S. Weber; M. Krautblatter; I. Hartmeyer; M. Keuschnig (The Cryosphere)
Rock slope instabilities and failures from permafrost rocks are among the most significant alpine hazards in a changing climate and represent considerable threats to high-alpine infrastructure. While permafrost degradation is commonly attributed to rising air temperature and slow thermal heat propagation in rocks, the profound impact of water flow in bedrock permafrost on warming processes is increasingly recognised. However, quantifying the role of water flow remains challenging, primarily due to the complexities associated with direct observation and the transient nature of water dynamics in rock slope systems. To overcome the lack of a quantitative assessment, we combine datasets of rock temperature measured in two deep boreholes (2016–2023), with electrical resistivity tomography measurements repeated monthly in 2013 and 2023; the site-specific temperature–resistivity relation determined in the laboratory with samples from the study area; and borehole piezometer data. Field measurements were carried out at the permafrost-affected north flank of the Kitzsteinhorn (Hohe Tauern range, Austria), which is characterised by significant water outflow from open fractures during the melt season. Borehole temperature data demonstrate a seasonal maximum of the permafrost active layer of 4–5 m. They further show abrupt temperature changes (∼ 0.2–0.7 °C) at 2, 3, and 5 m depth during periods with enhanced water flow and temperature regime changes between 2016–2019 and 2020–2022 at 10 and 15 m depth, which cannot be explained solely by conductive heat transfer. Electrical resistivity measurements repeated monthly reveal a massive decrease in resistivity from June to July and the initiation of a low-resistivity (< 4 kΩ m) zone in the lower part of the rock slope in June, gradually expanding to higher rock slope sections until September. We hypothesise that the reduction in electrical resistivity of more than an order of magnitude, which coincides with abrupt changes in borehole temperature and periods of high water heads up to 11.8 m, provides certain evidence of snowmelt water infiltration into the rockwall becoming pressurised within a widespread fracture network during the thawing season. This study shows that, in addition to slow thermal heat conduction, permafrost rocks are subjected to sudden push-like warming events and long-lasting rock temperature regime changes, favouring accelerated bottom-up permafrost degradation and contributing to the build-up of hydrostatic pressure, potentially leading to slope instability.